The Correlation Between Vocabulary Mastery And Reading Comprehension In English at SMP Negeri 4 Tondano - Sianturi, Enjelina; Mogea, Tini; Kumayas, Tirza A. (Program Studi Pendidikan Bahasa Inggris, 2025)
The purpose of this study is to investigate the potential relationship between vocabulary mastery and reading comprehension. The study was carried out at SMP Negeri 4 Tondano, with students in grades 8 B, which consist of a total of 26 students. A vocabulary mastery test and reading comprehension questionnaire with the (David, 1974) score were used to collect the data, which were then manually correlated using the Pearson Product-Moment method for analysis. The correlation coefficient, or r, between vocabulary mastery and reading comprehension is 0.783 according to the Pearson Product Moment Correlation Coefficient. The study's result indicates that vocabulary mastery at SMP Negeri 4 Tondano and reading comprehension are highly correlated. It was shown that there was a strong correlation between vocabulary mastery in English classes and their level of reading comprehension. It is required to students to actively seek out feedback from classmates and teachers